Estimates of association between cognitive complexity levels and creativity levels of field grade military officers: an exploratory study of the relationship - Clark, Chadwick W. (Kansas State University, 2008)
The purpose of this study was to investigate the association between cognitive complexity and creativity. This research was conducted with a sample (n = 126) of field grade officers at the Joint and Combined Warfighter School in Norfolk, VA, as part of class 08-02 (N = 250), in early 2008. The Department of Defense (DoD) challenges its officers to operate in ambiguity, solve complex problems and be creative. The DoD needs its officers to apply a creative imagination, supported by skill, knowledge, and experience, to design integrated operational plans that employ military forces. In order to do this, the DoD teaches its officers cognitive thinking skills and creativity at the same time. Are cognitive thinking skills and creativity correlated? Two valid and reliable tests were used to test for cognitive complexity and creativity: the Learning Environments Preference (LEP) and the Torrance Tests of Creative Thinking (TTCT), both the Figural-A and the Verbal-A forms. A small positive but statistically insignificant (τ = .083) correlation was found between the measured levels of cognitive development (LEP CCI) and the measured level of creativity (TTCT). In addition, this research analyzed the effect that branch of service, combat experience, gender, age, and education level had on creativity and cognitive complexity. There was a strong positive correlation between cognitive complexity and level of civilian education level ([Tau] = .345, p < .001). There was a strong positive correlation between creativity and level of civilian education level ([Tau] = .341, p < .001). When LEP CCI scores (cognition) were correlated to TTCT creativity scores while controlling for combat experience there was a medium positive correlation (r = .285, p = .007). When combat experience was correlated to the LEP CCI scores (cognition) there was a medium positive correlation ([Tau] = .246, p = .002). There was a medium positive correlation between military rank and LEP CCI (cognition) scores ([Tau] = .228, p = .002). There was a small positive correlation between military rank and TTCT creativity scores ([Tau] = .15, p = .042). When gender was correlated to the TTCT scores (creativity), there was a statistically significant positive correlation for females ([Tau] = .151, p = .041). A small positive but statistically insignificant (r = .111) correlation was present between the level of creativity, the level of cognitive development, and age. There was a small positive but statistically insignificant (r = .109) correlation between the level of creativity, the level of cognitive development, and branch of service.
Keywords: creativity; cognitive compleity; Education, Educational Psychology (0525)